The influence of timing of knee recurvatum on surgical outcome in cerebral palsy - Klotz, Matthias C. M.; Heitzmann, Daniel; Wolf, Sebastian Immanuel; Thielen, Mirjam; Maier, Michael Wolfgang; Dreher, Thomas (Research in developmental disabilities, 2016)
Recent reports have shown that timing of genu recurvatum (GR) might be caused by different underlying factors and that equinus leads to GR especially during early stance. The purpose of this study was to investigate the reduction of GR after surgical correction of equinus in children with bilateral spastic cerebral palsy and whether the children with early and late type GR show differences in reduction of knee hyperextension after a surgery. In 24 limbs (mean age 10.3 years, GMFCS I-III) showing equinus and GR the kinematics of the knee and ankle as well as the kinetics of the knee were evaluated before and one year (mean follow up period: 12.8 months) after surgical correction of equinus. The study was approved by the local ethical committee. Limbs with early type GR showed a reduction by 11.1° (p<0.001) and those with late type GR by 6.0° (p<0.049) in GR after surgery. Before surgery limbs with early type GR showed increased external extending moments, which decreased significantly after surgery. In contrast limbs with late GR did not show a significant reduction of those moments. The findings of this study underline the influence of equinus on early GR as an underlying factor. As equinus is attributed to early knee hyperextension and proximal factors are more important as underlying factors in late type GR, a classification into early and late onset GR is useful to identify underlying factors and to choose adequate treatment.